Does sex hormone-binding globulin cause insulin resistance during pubertal growth?. Issue 5 (May 2019) - Le, Shenglong; Xu, Leiting; Schumann, Moritz; Wu, Na; Törmäkangas, Timo; Alén, Markku; Cheng, Sulin; Wiklund, Petri
Abstract : Background: The directional influences between serum sex hormone-binding globulin (SHBG), adiposity and insulin resistance during pubertal growth remain unclear. The aim of this study was to investigate bidirectional associations between SHBG and insulin resistance (HOMA-IR) and adiposity from childhood to early adulthood. Methods: Participants were 396 healthy girls measured at baseline (age 11.2 years) and at 1, 2, 4 and 7.5 years. Serum concentrations of estradiol, testosterone and SHBG were determined by ELISA, glucose and insulin by enzymatic photometry, insulin-like growth factor 1 (IGF-1) by time-resolved fluoroimmunoassays, whole-body fat mass by dual-energy X-ray absorptiometry and HOMA-IR were determined by homeostatic model assessment. The associations were examined using cross-lagged path models. Results: In a cross-lagged path model, SHBG predicted HOMA-IR before menarche β = −0.320 (95% CI: −0.552 to −0.089), P  = 0.007, independent of adiposity and IGF-1. After menarche, no directional effect was found between SHBG and insulin resistance or adiposity. Conclusions: Our results suggest that in early puberty, decline in SHBG predicts development of insulin resistance, independent of adiposity. However, after menarche, no directional influences between SHBG, adiposity and insulin resistance were found, suggesting that observational associations between SHBG, adiposity and insulin resistance in pubertal children may be subject to confounding. Further research is needed to understand the underlying mechanisms of the associations between SHBG and cardiometabolic risk markers in peripubertal children.